The Bottom Two Percent: Using Positive Psychology to Create Change Among Convicts - Wittekind, Katie (2018)
We can turn convicted individuals into thriving members of the community. An empowering approach with the convicted will improve rehabilitative outcomes by creating behavior change. There exists a model that successfully rehabilitates the convicted by teaching the skills necessary to reenter society. This capstone uses the Delancey Foundation as a case study of this model. Delancey provides housing, job training, and education to convicts, addicts, and the homeless. Delancey uses social entrepreneurship and peer mentorship to empower residents. This capstone uses the research of positive psychology to demonstrate how Delancey converts takers into givers using peer mentorship, which develops the major components of human well-being described in Seligman’s PERMA model. Increased PERMA generates the conditions for convicts to thrive, ultimately becoming contributing members of society. This capstone makes formal recommendations for the replication of the Delancey model